The Role of Notary-PPAT in the Implementation of Tax Payment Fraud Prevention - Ade Kusumadewi; Gunarto Gunarto; Maryanto Maryanto (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2020)
This research has the following objectives: 1) To determine the role of the Notary/Land Deed Making Officer (PPAT) in the implementation of fraud prevention in connection with the Payment of Taxes/Tax Charges for Acquisition of Land and Building Rights (BPHTB) for the Implementation of the Process Sale and Purchase based on Authorization to Sell with the Object of the Sale and Purchase of Land and Buildings. 2) To find out the factors that arise to prevent fraud against fraud in the imposition of the tax burden on the acquisition of land and building rights (BPHTB). Method used in this research is empirical juridical method. Research using the empirical juridical method is research on the effect of the law on society. This study uses primary data sources and secondary data sources. Primary data sources are sources obtained from field research, while secondary data sources consist of primary legal materials, secondary legal materials, and tertiary materials. Then the data were analyzed qualitatively. The research results show that: 1) The authority of the recipient of the power of attorney cannot be proven in real or not valid, unless it is proven by the existence of a sale-purchase agreement (PPJB) which contains the word paid. Because then it can be proven that the party is really the buyer. If it is not attached with a Sale-Purchase Deed (PPJB), it is feared that it will be misused or used by those who wish. In accordance with Article 1320 (KUHPerdata) regarding the validity of an agreement between the power of attorney and the grantor of power. Where in the process of transfer of name or request for sale and purchase certificates due to the transfer of rights to land and buildings, one of the conditions that must be fulfilled by the cliet or certificate application is the settlement of tax payments, who are burdened with taxes in the process of transferring rights to land and buildings, namely Seller and Buyer. Buyers are subject to tax burdens in the form of Fees for Acquisition of Land and Building Rights (BPHTB). So the role of the Notary/PPAT Officer is very much needed to minimize the existence of fraud that can result in losses for the Notary/Land Deed Making Official itself. 2) Preventing Factors for Notary Officers or Land Deed Making Officials (PPAT) so that there is no misuse of the power of sale and purchase of land in relation to the tax burden on the acquisition of land and building rights (BPHTB), including: a) Making a statement letter under the above hand stamp 6000, and inserted in the document; b) Photos of the parties; c) Closed-Circuit Television (CCTV); d) Fingerprints of the parties; e) Receipt in full for the sale of land which must be written by the party itself; and f) Providing a moral message to the parties so that their actions are truly honest, containing: (1) That the sale and purchase is based on the principles of good faith and propriety; (2) Sale and Purchase conducted in a clear and cash manner; and (3) Please be honest about the number of transactions.